Cognitive training for people with mild to moderate dementia - Bahar‐Fuchs, Alex (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To evaluate the effects of cognitive training on cognitive and non‐cognitive outcomes for people with mild to moderate dementia and their caregivers. To compare the effects of cognitive training with those of other non‐pharmacological interventions, including cognitive stimulation or rehabilitation. To identify and explore factors related to intervention and trial design that may be associated with the efficacy of cognitive training.